2002
DOI: 10.1097/00005082-200201000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Cardiovascular Disease in Type 2 Diabetes: The Role of Antioxidants and Pro-Oxidants

Abstract: Oxidative stress occurs when there is an imbalance between free radical production and antioxidant capacity. This may be due to increased free radical formation in the body and/or loss of normal antioxidant defenses. Oxidative stress has been associated with the development of cardiovascular disease. The role of antioxidants in the primary and secondary prevention of coronary heart disease is currently under study. Although epidemiologic evidence indicates that antioxidants may decrease cardiovascular risk, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 84 publications
4
102
0
4
Order By: Relevance
“…Additional evidence suggested that impairment of endothelium-dependent vasodilatation is not a direct consequence of reduced activity/expression of eNOS, but is rather triggered by an enhanced inactivation of nitric oxide by oxidative stress, especially ROS [38]. Oxidative stress and impaired cardiac contractile function have been demonstrated in insulin-resistant states such as type 2 diabetes, hypertension and obesity [1,39]. A highfructose diet has been shown to reduce mRNA expression of antioxidant catalase [40], which itself provides solid support for a therapeutic indication of catalase enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence suggested that impairment of endothelium-dependent vasodilatation is not a direct consequence of reduced activity/expression of eNOS, but is rather triggered by an enhanced inactivation of nitric oxide by oxidative stress, especially ROS [38]. Oxidative stress and impaired cardiac contractile function have been demonstrated in insulin-resistant states such as type 2 diabetes, hypertension and obesity [1,39]. A highfructose diet has been shown to reduce mRNA expression of antioxidant catalase [40], which itself provides solid support for a therapeutic indication of catalase enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In the body exist various antioxidant molecules to be used against free radicals injury. Among them, glutathione and the enzymes superoxide dismutase and glutathione peroxidase are critical for maintaining the redox balance of the cell [6][7]. However, this balance may be destroyed by certain vascular features, such as by certain risk factors for atherosclerosis including hypertension, hyperlipidaemia, diabetes and cigarette smoking [2].…”
Section: Oxidative Stress Endothelial Dysfunction and Atherosclerosismentioning
confidence: 99%
“…This is followed by events involved in the atherosclerotic plaque formation such as inflammatory responses, cell proliferation and remodelling of the vasculature and finally to vascular lesion formation, plaque rupture, thrombosis and tissue infarction [1]. A causative relationship exists between these features and oxidative stress in the vessel wall, as pathological events crucial in the onset and progression of vascular disease such as oxidation of LDL, reduction of nitric oxide (NO) bioavailability and vascular inflammation are all modulated by oxidative stress and free radicals generation [2,3].Moreover, to counteract the effect of reactive species, cells are endowed with a complex antioxidant network that operate to prevent or limit oxidant damage [6,7]. In particular, oxidative stress occurs when there is an imbalance between free radical production and antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that increased free-radical mediated oxidative stress is associated with diabetic complications in both humans and animals [4,[12][13][14][15][16]. Reactive Oxygen Species (ROS) or Free Oxygen Radicals (FOR's) such as superoxide radical (O 2 -), hydroxyl radical (OH -), and hydrogen peroxide (H 2 O 2 ), generated during oxygen metabolism, are controlled by various cellular defense mechanisms consisting of enzymatic [(superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSHPx)] and non-enzymatic (vitamin E, β-carotene, vitamin C) antioxidants [17].…”
Section: Introductionmentioning
confidence: 99%